The critical role of IL-23 receptor positive T cells in the pathogenesis of anterior uveitis associated with spondyloarthropathy - Hedley, R (2021)
The spondyloarthropathies (SpAs) are a group of chronic inflammatory diseases which predominantly affect the joints of the axial skeleton. However, many patients with SpA may have extra-articular manifestations within the skin and gut. Pathology of SpA in all of these tissues has been shown in recent studies to be driven by local resident populations of interleukin (IL)-23 responsive cells. The eye is also involved in these diseases, with uveitis occurring in up to 40% of patients with SpA. Therefore, it is feasible that a resident population of IL-23 responsive cells could also exist within the eye.